Safety of heterologous ChAdOx1-S/BNT162b2 primary schedule versus homologous BNT162b2 vaccination: Insights from an Italian post-marketing study, 2021 - Francesca Fortunato; Rosa Prato; Giuseppina Iannelli; Leonardo Ascatigno; Daniela Loconsole; Pier Luigi Lopalco; Domenico Martinelli (Taylor & Francis Group, 2023)
During COVID-19 vaccination campaign, possible ChAdOx1-S-associated risks of thrombosis with thrombocytopenia syndrome led to implement ChAdOx1-S/BNT162b2 heterologous vaccination, despite the limited information on its reactogenicity and safety. We conducted a prospective observational post-marketing surveillance study to assess the safety of this heterologous schedule. A casually selected sample of recipients (n: 85; age: 18-60 years) of ChAdOx1-S/BNT162b2 at the vaccination hub of the Foggia Hospital, Italy, was matched with an equal sample of recipients of homologous BNT162b2. Safety was evaluated 7 days, 1 month and 14 weeks after the primary vaccination series using an adapted version of the "V-safe active surveillance for COVID-19 vaccine safety" CDC standardized questionnaire. After 7 days, local reactions were highly frequent (>80%) in both groups, and systemic reactions were less common (<70%). Moderate or severe pain at the injection site (OR = 3.62; 95%CI, 1.45-9.33), moderate/severe fatigue (OR = 3.40; 95%CI, 1.22-9.49), moderate/severe headache (OR = 4.72; 95%CI, 1.37-16.23), intake of antipyretics (OR = 3.05; 95 CI%, 1.35-6.88), inability to perform daily activities and work (OR = 2.64; 95%CI, 1.24-5.62) were significantly more common with heterologous than homologous vaccination. No significant difference in self-reported health status was recorded 1 month or 14 weeks after the second dose with BNT162b2 or ChAdOx1-S/BNT162b2. Our study confirms the safety of both heterologous and homologous vaccination, with a slight increase in some short-term adverse events for the heterologous regimen. Therefore, administering a second dose of a mRNA vaccine to the recipients of a previous dose of viral vector vaccine may have represented an advantageous strategy to improve flexibility and to accelerate the vaccination campaign.